2017
DOI: 10.1103/physrevapplied.7.024005
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Approach to Electroresistance in Ferroelectric Tunnel Junctions

Abstract: In this paper, a theoretical approach comprising the nonequilibrium Green's function method for electronic transport and the Landau-Khalatnikov equation for electric polarization dynamics is presented to describe polarization-dependent tunneling electroresistance (TER) in ferroelectric tunnel junctions. Using appropriate contact, interface, and ferroelectric parameters, the measured current-voltage characteristic curves in both inorganic (Co=BaTiO 3 =La 0.67 Sr 0.33 MnO 3 ) and organic (Au=PVDF=W) ferroelectri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
(88 reference statements)
1
25
0
Order By: Relevance
“…Figures 3(a) and (b) show the transient voltage response in each layer for both high-k and FE MOS capacitors, respectively, and it can be immediately observed that the main difference between high-k and FE capacitors is the opposite sign of voltage drops across the high-k and FE layers in the steady state. Also, under the steady state, one can see that the direction of field across the FE oxide in the case of charge boost is opposite to that of polarization, which is the main feature of depolarization [14]. Hence, to achieve the inversion charge boost in the steady state, the field across the FE oxide has to be dominated by the depolarization, rather than the applied bias, which is also consistent to the thermodynamic picture given in Ref.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Figures 3(a) and (b) show the transient voltage response in each layer for both high-k and FE MOS capacitors, respectively, and it can be immediately observed that the main difference between high-k and FE capacitors is the opposite sign of voltage drops across the high-k and FE layers in the steady state. Also, under the steady state, one can see that the direction of field across the FE oxide in the case of charge boost is opposite to that of polarization, which is the main feature of depolarization [14]. Hence, to achieve the inversion charge boost in the steady state, the field across the FE oxide has to be dominated by the depolarization, rather than the applied bias, which is also consistent to the thermodynamic picture given in Ref.…”
supporting
confidence: 86%
“…V si is the silicon surface potential drop and V f b is the flat-band voltage given as φ 1 − φ 2 − E f,metal − δ with φ 1 and φ 2 being conduction band discontinuities at the metal/FE and DE/silicon interfaces, respectively, E f,metal is the Fermi energy of metal, and δ is the energy difference between conduction band and Fermi level in the quasi-equilibrium region of p-type silicon. For a given ρ s , V metal and V DE are given as [14] V…”
mentioning
confidence: 99%
“…In Eq. 13, the potential energy drop within the metal is described under the Thomas-Fermi approximation [25]. For a given E F E .…”
Section: Theoretical Modelmentioning
confidence: 99%
“…39 In a recent paper, the NEGF method and the Landauer formula were used to model I-V curves of step barrier FTJs. 40 The results suggest that both the height and thickness of a CoO x buffer layer forming at the Co/BaTiO 3 interface may change under bias.…”
Section: Modeling Of Tunneling Currents In Ftjsmentioning
confidence: 91%